Analysis of Work Motivation, Work Discipline, and Work Environment on Employee Performance in Public Companies in the Medan City Market Region - Hermi Hafsari Hasibuan; Muhammad Toyib Daulay (Yayasan Multidimensi Kreatif, 2024)
This study aims to evaluate the impact of work motivation, discipline, and work environment on employee performance in the Medan City Market Regional Public Company. This study uses a quantitative approach with a double linear regression analysis technique processed using SPSS Version 27 software, involving 88 participants and collecting data through questionnaires. The results of the study show that the three variables (Work Motivation, Work Discipline, and Work Environment) have a positive and significant impact on employee performance, both individually and simultaneously. Among the three variables, the Work Environment is proven to have the greatest influence on improving employee performance.